Pengaruh Karakteristik Permukaan Lahan Terhadap Informasi Spektral Hamburan Balik Radar Pada DaerahPerkotaan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
This research was conducted to assess the influence of the return surface features characteristics of Cilacap City to the radar .,.return (backscatter) energy. The Radarsat digital data acquired on ',August 1997, color aerial photographs on May 5th 1999 at scale 1 : i 20,000 and field data were used in the experiment. The relation of pixel value (DN) of Radarsat data with the percentage of object coverage in the study area and the direction C'd it to the sensor were studied. The percentage of object coverage in the study area was extracted from aerial photo and the `direction of it to the sensor was known from ground observation. , . 1., The correlation and linier regression analysis .produce the &#61492